ANALISIS TINGKAT KEMATANGAN PENYEDIAAN TATA KELOLA TEKNOLOGI INFORMASI DI PDII LIPI MENGGUNAKAN FRAMEWORK COBIT 4.1 - Octavia, Rima (BACA: Jurnal Dokumentasi dan Informasi, 2014)
Centre for Scientific Documentation and Information – Indonesian Institute of Science (PDII LIPI) began to developbusiness objectives towards a digital library. To support this goal should be held IT governance while PDII LIPI hasno specific IT governance. This research aims to study the condition of the IT management and determine the levelof maturity of the provision of IT governance framework based on COBIT 4.1. COBIT is one of the internationalstandard for IT governance. COBIT is used in this study were able to measure the COBIT 4.1 for organizations thatdo not use IT governance. Analysis of the level of maturity of the provision of IT governance is based on aquestionnaire that is processed by the COBIT 4.1 framework and compared with the actual conditions in the ITmanagement in PDII LIPI. The results of the calculation of the maturity level of to provided IT governance in PDIILIPI based on framework COBIT 4.1 shows that PDII-LIPI already at level 3 (Defined Process). This is consistent withthe actual conditions in PDII-LIPI. COBIT 4.1 is considered quite capable, reliable and easy to implement in PDII LIPI.